2020
DOI: 10.1101/2020.07.07.186791
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Independence of 3D chromatin conformation and gene regulation during Drosophila dorsoventral patterning

Abstract: ABSTRACTThe relationship between the 3D organisation of chromatin inside the nucleus and the regulation of gene expression remains unclear. While disruption of domains and domain boundaries can lead to mis-expression of developmental genes, acute depletion of key regulators of genome organisation, such as CTCF and cohesin, and major reorganisation of genomic regions have relatively small effects on gene expression. Therefore, it is unclear whether changes in gene expression and… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 137 publications
(196 reference statements)
1
6
0
Order By: Relevance
“…Notably, stable TAD structures observed in these primary tissues contrast previous reports of chromatin organization in cell lines derived from prostate cells 44,62 , highlighting the necessity of low-input protocols and primary tissues 40 . Our findings further support recent reports of shared higher-order chromatin organization among phenotypically distinct cell types in model organisms 2,28,32,[63][64][65] . Taken together, this body of evidence suggests that large disruptions to TADs and compartments may constrain the transformation of normal to cancer cells or the divergent subtyping within prostate tumours.…”
Section: Discussionsupporting
confidence: 92%
“…Notably, stable TAD structures observed in these primary tissues contrast previous reports of chromatin organization in cell lines derived from prostate cells 44,62 , highlighting the necessity of low-input protocols and primary tissues 40 . Our findings further support recent reports of shared higher-order chromatin organization among phenotypically distinct cell types in model organisms 2,28,32,[63][64][65] . Taken together, this body of evidence suggests that large disruptions to TADs and compartments may constrain the transformation of normal to cancer cells or the divergent subtyping within prostate tumours.…”
Section: Discussionsupporting
confidence: 92%
“…On the one hand, cohesin-mediated enhancer-promoter loops across cell lines correlate with gene expression [96] and mutations to the cohesin complex result in loss of gene expression [97]. On the other hand, multiple studies have shown that changes in TAD organization do not translate to changes in gene expression [98,99].…”
Section: Box 1 Enhancer Features Function and Identificationmentioning
confidence: 99%
“…Furthermore, even in the case when a promoter has a 3D contact with a regulatory sequence, less than 10% of genes display differential expression when the contact is lost, but the same is true at maintained loops. This suggests that the presence of chromatin loops would not be essential for controlling gene transcription in the majority of cases 58,[63][64][65] .…”
Section: Chromatin Loops and Gene Regulationmentioning
confidence: 99%